Genetic polymorphism within Activating Transcription Factor 4 gene in Sahiwal cattle - Mir, Mohsin Ayoub; Ganai, Abdul Majeed; Ahmad, Tavsief; Magotra, Ankit; Pandit, Arif; Singh, Arun Pratap; Arya , Ashwani; Singh, Manvendra (Journal of Livestock Biodiversity, 2025)
Major focus of dairy cattle genomics is to identify genes underlying the genetic variability of economically important traits that could be useful in breeding programmes. The present study on 130 Sahiwal cows by PCR-RFLP and sequencing aimed to explore the polymorphism in the entire coding region of ATF4 gene. Nucleotide sequences were visualized and edited using BioEdit software. The multiple sequence alignments of the edited sequence with corresponding reference sequences were performed with ClustalW software to identify SNPs. Nucleotide sequences were translated to amino acids by ExPASy Translate tool, edited, and subjected to multiple sequence alignment with the reference ATF4 protein sequences of Bostaurus. Amino acid substitutions were analysed using SIFT software (sift.jcvi.org/ or sift-dna.org/). Four set of primers exhibited total 04 SNPs T352C in intron 1, G379A in exon2, A215T and A230C in exon 3 including 02 transitions and 02 transversions. Primer 4 exhibited monomorphic pattern. The identified SNPs can be used as markers for milk traits in Sahiwal cattle. However, association and validation are warranted on larger number of animals and in different herds of Sahiwal cattle.